Profile of Peri-urban and Rural Dairy Farmers : A Comparative Analysis - Kamta Prasad Dwivedi , Arun Kumar; Prakash Singh (Indian Journal of Extension Education, 2014)
This study was conducted in Faizabad district of Uttar Pradesh to study the socio-economic profile of peri-urban and rural dairy farmers with a sample of 120 dairy farmer (60 peri-urban + 60 rural) selected from eight villages selected through probability proportionate sampling technique on the basis of herd size. The study revealed that the majority of peri-urban (88.33%) and rural dairy farmers (75%) were literate with the dominancy of joint family system (68.33% in peri-urban and 65% in rural). The majority of peri-urban dairy farmers (63.33%) and rural dairy farmers (56.66%) were found to be medium size family i.e. 5-8 members; and possessed pucca house 65 per cent and 61.66 per cent, respectively. The majority of both type of farmers (90% and 78.33%) reported agriculture as their main occupation. Amajority of the periurban dairy farmers (46.66%) was found to be having marginal land holding, while rural dairy farmers (33.33%) were found in each marginal and large land holding categories. The annual income of majority of the peri-urban and rural dairy farmers (45% and 40%) was found in the category of ` 60,001/- to 90,000/- and 30,000/-1 to 60,000/- respectively. The dominant mass media information sources were observed to be radio followed by mobile and television. Majority of periurban dairy farmers (55%) and rural dairy farmers (73.33%) were observed to be in the medium category of material possession. The medium level of scientific orientation, achievement motivation, economic motivation and value orientation were found among both type of respondents.